Ethnography step-by-step - Fetterman, David M. (Applied social research methods series, 2020)
"This popular text has a "how to" and "here's what you need to do approach" to ethnographic research, taking the mystery out of the research process and making ethnography accessible to students. The author's applied background influences his discussion of ethnography from the first step to last. This text benefits from the inclusion of interesting examples from David M. Fetterman's experience that help novice researchers understand the concepts being addressed. The Fourth Edition includes new examples from the author's work; more on use of new digital tools; expanded discussions of culture, contextualization, emic and etic distinctions, and symbols; updated sections on theory; and Questions for Reflection at the end of each chapter."--Provided by publisher.